Synergistic effect of Ni(OH)2 and MXene nanosheets in 3D framework on the improvement of dielectric, energy storage, mechanical and thermal characteristics of polyvinylidene fluoride(PVDF) polymeric composites - Dizayee, Wala; M. Hamarashid, Mayyada; Zorah, Mohammed; M.A. Mahmoud, HassabAlla; Al-Bahrani, Mohammed; Taki, Anmar Ghanim; Abdulkareem-Alsultan, G.; Nassar, Maadh Fawzi (Elsevier, 2024)
This work introduces a novel method for incorporating meticulously designed nanohybrids to improve the dielectric characteristics of polymer composites. Conventional ceramic fillers have problems with dispersion even if they are good at increasing permittivity. Here, we overcome this constraint by creating nanohybrids made of MXene, polyvinylidene fluoride (PVDF), and single-layered and three-dimensional Ni(OH)2. An essential coupling agent, polyethyleneimine (PEI), fosters a robust electrostatic connection between Ni(OH)2 and superior adhesion with MXene. Using only 9.5 wt percent filler loading, we are able to achieve a low loss tangent (tan δ=0.4) at 1 kHz with a considerable permittivity improvement (ε=1000) thanks to this creative design. The nanohybrid structure's ability to promote longer interfacial contact is crucial to this enhancement. Moreover, the integrated Ni(OH)2 layer functions as a semiconductor, obstructing the passage of current through the MXene flakes and lowering conductivity overall. At a low Ni(OH)2/MXene loading of 1.5 wt%, our three-phase composites also show higher dielectric strength (248.68 MV/m). Specifically, the synergistic coupling of MXene with Ni(OH)2 provides notable increases in mechanical and thermal properties. The tensile strength and Young's modulus of these films are much higher than those of virgin PVDF and Ni(OH)2-modified composites. © 2024 Elsevier B.V.